Karsinoma Endometrium pada Seorang Pasien dengan Diabetes Mellitus Tipe 2: Laporan Kasus: Laporan Kasus - Teron, Thomas Aquinas Ehe; Nugraha, Ida Bagus Aditya; Gotera, Wira; Daniella, Dian; Riandika, Gede Vendi Cahyad (Cermin Dunia Kedokteran, 2026)
Introduction: Endometrial cancer is often associated with obesity, type 2 diabetes mellitus (T2DM), insulin resistance, and hyperinsulinemia. Case: A 71-year-old woman with a history of T2DM, hypertension, and obesity (body mass index/BMI 32.08 kg/m²) presented with intermittent abdominal pain and vaginal bleeding. She had undergone a curettage procedure two weeks earlier. Ultrasound examination revealed a hyperechoic mass in the uterine corpus, and histopathological examination following staging laparotomy confirmed type 2 endometrial carcinoma (high-grade serous carcinoma) with omental metastasis. The diagnosis was stage IVB endometrial carcinoma. During hospitalization, the patient received intravenous ceftriaxone, insulin glargine, and oral antihypertensive medications (ramipril and nifedipine). She was scheduled to receive systemic chemotherapy with carboplatin and paclitaxel, the standard regimen for advanced-stage, aggressive non-endometrioid endometrial cancer. Discussion: Diabetes mellitus, particularly when accompanied by chronic hyperglycemia, insulin resistance, and hyperinsulinemia, is associated with an increased risk of various cancers, including endometrial cancer, as well as a poorer prognosis. Factors such as obesity, age, estrogen exposure, and insulin therapy may exacerbate this risk, while biomarkers such as IGF-2 and IGFBP-3 have the potential to be used for early detection and risk assessment of endometrial cancer. Conclusion: This case highlights the strong link between T2DM, obesity, and aggressive endometrial cancer, emphasizing the importance of early detection and comprehensive management in patients with metabolic risk factors.